Establishment of Reference Interval for TSH in Pregnant Georgian Women - Tamar Peshkova; Elene Giorgadze; Lasha Uchava; Koba Kamashidze (International Journal of Medical Research and Review, 2015)
Introduction: Maternal thyroid dysfunction has been associated with variety of adverse maternal and fetal outcomes. Due to many physiological changes during pregnancy, interpretation of thyroid function tests needs trimester-specific reference intervals for a specific population. Aim of this study was to determine the second trimester-specific reference interval for thyroid-stimulating hormone (TSH) in healthy pregnant Georgian women.Methods: 2876 pregnant women were admitted to Batumi Maternity House (BMH) from January 2009 to December 2011 for second trimester routine prenatal examination, including TSH screening. Standardized information regarding thyroidal, obstetric and general medical status of women was collected. The reference interval for TSH, based on 2.5th and 97.5th percentiles, was calculated from thyroid dysfunction risk free pregnant women.Results: Derived reference interval for TSH in the second trimester of pregnancy was 0.21–4.1 mIU/L and it was significantly different from the reference intervals recommended by American Thyroid Association (ATA) and the reference interval provided by manufacturer for non-pregnant adults.Conclusion: We calculated clinically relevant trimester-specific reference interval for TSH in order to facilitate detection and improve management of thyroid dysfunction in Georgian pregnant women.